A descriptive study to assess the knowledge and practice regarding menstrual hygiene among adolescent girls of Government School of Shimla, Himachal Pradesh - Anjali Mahajan; Kanica Kaushal (Wolters Kluwer Medknow Publications, 2017)
Introduction: Adolescent girls belong to vital age group, not only because they are the entrant population to motherhood but also because they are threshold between childhood and motherhood. The girls should be educated about significance of menstruation and development of secondary sexual characteristics, selection of sanitary menstrual absorbent and its proper disposal. Aims and Objectives: The objectives of the present study were to assess the existing knowledge and practice regarding menstrual hygiene among adolescent girls and to determine the co-relation of knowledge and practice score among the adolescent girls. Materials and Methods: The study conducted was a descriptive cross sectional study done on 100 adolescent girls from class 9th to 12th of Govt. Girls School in Shimla, Himachal Pradesh (Convenience sampling). Prior to the commencement of the study, they were explained the purpose and nature of the study. Information on demographic variables which include age, class, type of family, education of mother, family income, age of menarche were collected from the participants. Results: The data on knowledge scores revealed that 29% had adequate knowledge about menstrual hygiene, 71% had inadequate knowledge about menstrual hygiene. The data revealed on practice scores revealed that 19%, 69%, 12% samples had poor, fair and good score of practices regarding menstrual hygiene respectively. Knowledge and practice scores of participants shows positive correlation between the two scores (*P < 0.001). Conclusion: Lack of information about menstrual hygiene can be attributed to various factors which need to be studied separately. The above findings reinforce the need to encourage safe and hygienic practices among the adolescent girls and bring them out of traditional beliefs, misconceptions and restrictions regarding menstruation. The investigators improved the general awareness about cause of menstruation and the organs involved. Use of sanitary napkins was promoted and various schemes regarding menstrual health were briefed to the students. Early awareness can prevent students from suffering from the various reproductive tract infections.